Resistance genomics and molecular epidemiology of high-risk clones of ESBL-producing Pseudomonas aeruginosa in young children - Patil, Sandip; Chen, Xiaowen; Dong, Shaowei; Mai, Huirong; Lopes, Bruno Silvester; Liu, Sixi; Wen, Feiqiu (Frontiers in Cellular and Infection Microbiology, 2023)
The emergence of multi-drug-resistant Pseudomonas aeruginosa poses a global threat. We studied the molecular epidemiology and antibiotic resistance mechanisms in 294 clinical isolates of P. aeruginosa from a paediatric hospital. Non duplicate isolates were recovered from clinical cases and were identified using an API-20 kit and followed by antimicrobial susceptibility testing was performed using the VITEK®2 compact system (BioMerieux, France) and broth dilution method. In addition, double-disc synergy test for ESBL was performed. Furthermore, β-lactamases, plasmid types and sequence types were determined by PCR and sequencing. 56% (n=164) isolates were resistant to piperacillin-tazobactam followed by cefepime 40% (n=117), ceftazidime 39% (n=115), imipenem 36% (n=106), meropenem 33% (n=97), ciprofloxacin 32% (n=94). 42% (n=126) isolates were positive for ESBL by double-disc synergy test. The blaCTX-M-15 cephalosporinase was observed in 32% (n=40/126) while 26% (n=33/126) were positive for blaNDM-1 carbapenemase. Aminoglycoside resistance gene aac(3)IIIa was observed in 16% (n=20/126) and glycylcycline resistance gene tetA(Aa) in 12% (n=15/126) of the isolates. A total of 23 sequence types were detected, ST1963, 12% (n=16) followed by ST381, 11% (n=14); ST234, 10% (n=13; ST145, 58% (n=10); ST304, 57% (n=9); ST663 5% (n=7) and a novel strain. In ESBL-producing P. aeruginosa, 12 different Incompatibility groups (Inc) were observed, the most common being IncFI, IncFIS and IncA/C. The MOBP was the most common plasmid type followed by MOBH, MOBF and MOBQ. The spread of antibiotic resistance is likely due to clonal spread and circulation of different plasmids in clinical strains of P. aeruginosa.